SEARCH FOR IDENTITY IN THE LITERARY WORKS OF ARUN JOSHI - Dr. Seraj Ud Din Pandith (Galaxy International Interdisciplinary Research Journal, 2023)
The central characters in the novels by Arun Joshi encounter diverse challenges throughout their life journeys. These challenges can stem from societal, psychological, political, cultural, spiritual, or inherent sources of pressure. These external forces hinder their ability to live as they desire, causing them to become entangled in the complexities of existence. Nevertheless, each of these characters embarks on a personal exploration to rediscover their true selves and reclaim what they’ve lost. This paper delves into their experiences of adversity, explores the origins of their struggles, and assesses the extent to which their endeavors to reconnect with their authentic selves prove fruitful.